Sistem Pendukung Keputusan Sistem Pendukung Keputusan Pemilihan Duta Baca Perpustakaan Ibrahimy dengan Metode Simple Additive Weighting (SAW) - Aries Zuhud (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Ibrahimy Library is a library owned by Ibrahimy University. In an effort to enhance the presence of Ibrahimy Library, there is currently a plan to organize a selection of library ambassadors. The primary goal of this activity is to provide recognition and motivation to students who demonstrate exceptional reading enthusiasm. Due to the complexity of selecting library ambassadors, which must meet several criteria, Ibrahimy Library plans to leverage information technology advancements, particularly by using a decision support system. The criteria that have been approved by the library include GPA, number of visits, written works, organizational experience, and personality. The decision support system is built using the Simple Additive Weighting (SAW) method, which involves finding the weighted sum of performance ratings for each alternative across all attributes. The final result of this system indicates that the student named Ibnu Aros, with a preference score of 1, is chosen as the library ambassador for Ibrahimy Library